Ri-abitare gli spazi: immaginari, utopie e pratiche in trasformazione - Francesca Bianchi (Cambio)
Today our daily life appears a multifaceted and articulated mix of ordinary and extraordinary, stability and change: a context inside which a range of latent “possibilities” is nested, on which human creativity committed to building the future seems to find expression (Jedlowski 2017, Augé 2012, Appadurai 2014). Investigating the theme of spaces and living has a lot to do with reflection on change – and on the subject’s ability to imagine and build the future – because it implies questioning a world that is changing and arouses new expectations and needs. Compared to a period in which, in our country, (little or) almost no reflection was carried out on this phenomenon, the house today appears (to be) one of the universal places from which to try to rethink ourselves and the word we live in. This essay will consider the contribution that some innovative collaborative housing practices, including co-housing, seem to offer to the rethinking of urbanity. Such practices in fact make explicit the inclination to be open to others, the aspiration to care, to feel in tune with the neighbourhood and surrounding spaces, and more generally with the world, in a perspective of trust towards the future.